Chrysanthemum Morifolium Extract And Ascorbic Acid-2-Glucoside (AA2G) Blend Inhibits UVA-Induced Delayed Cyclobutane Pyrimidine Dimer (CPD) Production In Melanocytes - Yim S; Lee J; Jo H; Scholten J; Willingham R; Nicoll J; Baswan SM (Dove Medical Press, 2019)
Sunghan Yim,1 Jeesun Lee,2 Hae Jo,2 Jeff Scholten,1 Ryan Willingham,3 Jim Nicoll,3 Sudhir M Baswan4 1Analytical Sciences R&D, Amway Corporation, Ada, MI, USA; 2Asia Innovation Center, Global Discovery R&D, Amway Corporation, Seoul, South Korea; 3Zen-Bio, Inc., Research Triangle Park, Durham, NC, USA; 4Global Discovery R&D, Amway Corporation, Ada, MI, USACorrespondence: Sunghan YimAmway Corporation, 7575 Fulton Street E, Ada, MI 49355, USATel +1 616 787 1458Fax +1 616 787 4466Email sunghan.yim@amway.comBackground: Solar ultraviolet radiation (UV) induces DNA damages in skin via direct absorption of UVB or indirectly by photosensitization mediated through UVA. Recent findings have revealed that UVA induces cyclobutane pyrimidine dimer (CPD) generation via chemiexcitation in melanocytes hours after the exposure. This UVA-induced delayed CPD (dark CPD) constitutes the majority of CPD in melanocytes. These findings indicate that sun light can damage the skin hours after the exposure, suggesting the need for skin care products post sun exposure. The main objective of this study was to investigate whether a blend of Chrysanthemum Morifolium flower extract (Chrys) and vitamin C derivative, Ascorbic Acid-2-Glucoside (AA2G), can provide protective effects against reactive oxygen species, melanin formation and UVA-induced dark CPD.Methods: Intracellular ROS levels were measured in epidermal keratinocytes using DHR123 dye. Melanogenesis inhibition efficacy was determined using B16 cells. As for the dark CPD measurement, Melan-a cells were treated with or without actives for 6 days, then irradiated with UVA at various doses. Cells were exposed with anti-CPD mAb followed by secondary Ab. CPD levels were determined by measuring fluorescent intensity using a high content imaging analysis.Results: Chrys, AA2G and their blend at various concentrations demonstrated ROS scavenging activity. Though Chrys alone did not show significant melanogenesis inhibition in B16 assay, the blend of Chrys with AA2G demonstrated additive effects in comparison with AA2G alone. The blend of AA2G and Chrys at various concentrations exhibited enhanced efficacy for inhibiting dark CPD compared to AA2G alone.Conclusion: The results from this study indicate that the use of natural antioxidant, Chrys in combination with AA2G, provides protection against UVA-induced delayed CPD formation by enhancing ROS scavenging activity and melanogenesis inhibition. These findings could potentially be applied for formulating post-sun exposure skin care products, possibly extending to evening-after care products.Keywords: cellular DNA photodamage, chrysanthemum morifolium extract, ascorbic acid-2-glucoside, AA2G, DNA damage, cyclobutane pyrimidine dimers, CPD, dark CPD, melanocytes